Flight performance of pollen starved honey bees and incomplete compensation through ingestion after early life pollen deprivation - Brodschneider, Robert; Omar, Eslam; Crailsheim, Karl (Frontiers in Physiology, 2022)
We investigated the effect of adult honey bee pollen nutrition on the flight performance of honey bees. Therefore, caged bees were allowed to perform 30 minutes of defecation / training flights every second day before flight performance of pollen-fed bees and pollen-deprived bees older than 16 days were compared in a flight mill. We first fed 10µl of 1M glucose solution to bees, and after they metabolized this during flight, they were fed 10µl of 2M glucose solution for a second flight test. Pollen-deprived bees flew longer and further than pollen-fed bees in both flights. Pollen-fed bees flew faster in the early period at the beginning of flights, whereas pollen-deprived bees were faster in the final phases. Pollen-fed bees were able to raise their maximum flight speed in 2M glucose solution flights, whereas pollen-constraint bees were not. The two groups did not differ in abdomen fresh weight, but the fresh weight of the head and thorax and dry weight of the head, thorax and abdomen were higher in pollen-fed bees. In a second experiment, we constrained pollen consumption of caged bees during the first seven days and compared daily consumption of bees from day 8 to 16 to consumption of bees unrestricted in pollen. We found that pollen-deprived bees perceive the pollen shortage and try to compensate for their needs by consuming significantly more pollen at the later phase of their life than pollen-fed bees of the same age. Still, bees constrained from pollen in the first seven days did only reach 51.1% of the lifetime consumption of unconstrained bees. This shows that bees can sense the need for essential nutrients from pollen, but their physiological apparatus does not allow them to fully compensate for their early life constraint. Pollen deprivation only in the first seven days of worker life likewise significantly reduced fresh and dry weights of the body sections (head, thorax, and abdomen) and survival. This underlines the importance of protein consumption in a short critical period early in adult bees’ lives for their development and their performance later in life.